ANALYSIS OF JOB SPECIALIZATION TOWARD EMPLOYEES (CASE STUDY: DINAS PERUMAHAN KAWASAN PERMUKIMAN DAN PERTANAHAN DAERAH) - Tuela, Novaldy; Pangemanan, Sifrid S.; Arie, Fitty Valdi (Universitas Sam Ratulangi, 2021)
Job specialization involves breaking down a task to its lowest level and designing jobs around each part. This creates specialization, expertise, and improved quality. Many studies on specialization works and practice are carried out in private organizations even though specialization can be applied in all field professions. The purpose of this study is to find out regarding job specializationâ€™s effect on employees. This study uses a qualitative method and interviews with informants were conducted to gain information regarding the phenomenon. The findings of this study show that employees uphold their duties and responsibilities professionally, other factors like the superior evaluations and the clients' satisfaction rates also played a large role for the workers to keep their performance stable. Recommendations proposed and found within this research based on the result and analysis are to maintain a good environment within the workplace. The other is to keep and cultivate the mentioned factors such as skills, experiences, and knowledge to increase the work's production rates by accomplishing the entrusted jobs efficiently.Â Â Keywords: Human resource management, job types, job description, division of labor, job specialization